PENGEMBANGAN SISTEM INFORMASI MANAJEMEN ABSENSI KARYAWAN PADA PT KALLA INTI KARSA - Aditya Perdana, A. Muh. Alief; Putra, Anhar Dana (Politeknik STIA LAN Makassar, 2024)
PT Kalla Inti Karsa is a part of the Kalla Group, a commercial property company that has successfully operated a number of shopping malls, offices, and industrial sectors in Makassar and its surrounding, including Ratu Indah Mall, Nipah Park, and Wisma Kalla Office Building. At PT Kalla Inti Karsa, the process of calculating total staff absences each month remains unchanged. Based on these issues, the objective of this study was to make the monthly attendance management process easier for both the administrator in charge of controlling employee attendance and all employees who participate in the attendance process. This study applied a qualitative approach. Researchers employ data reduction, data display, and conclusion drafting as data analysis methodologies. This study employed both primary and secondary data, as well as source triangulation techniques to assure the accuracy of the data and information gathered. The output of this study produced application designs for administrators to manage employee attendance and applications for employees to perform attendance activities. During the application design process, researchers used the PHPMyAdmin programming language as well as five information system components: hardware, software, database, procedures, and people.